Cutaneous melanoma in a red-footed tortoise (Chelonoidis carbonaria) - De Santi, Mariele [UNESP] (2020)
There are few clinical reports of melanomas in reptiles. A 10-year-old male red-footed tortoise (Chelonoidis carbonaria) was referred to the Veterinary Hospital presenting with an ulcerated mass in the lateral aspect of the left pelvic limb. Radiographs demonstrated swelling and increased soft tissue density overlying the femur, tibia, and fibula, without bone involvement. Fine-needle aspiration cytology revealed innumerable round cells, with a defined cytoplasm filled with fine brown-black granules (melanin), which were considered well-differentiated melanocytes, suggesting a case of cutaneous melanoma. The mass was surgically removed. It was encapsulated and had an abundant blood supply. Histopathological examination revealed a well demarcated and encapsulated neoplastic proliferation of mesenchymal cells, with high cellularity and moderate fibrous stroma. Lymphangiectasia in the dermis adjacent to the tumor was also observed. Immunohistochemistry confirmed the diagnosis, with cells staining positive for Melan-A antibody being observed in neoplastic proliferation, adjacent dermis, inside lymphatic vessels, and invading the delimiting tumor's capsule. There was no evidence of local or systemic recurrence of the neoplasm over 500 days after removal. Chelonians can be affected by cutaneous melanomas. Surgical removal in this case was curative.